2022
DOI: 10.3390/vaccines11010082
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response after Two Doses of BNT162b2 mRNA Vaccine Has a Role in Predicting Response after Three Doses That Is Related to Plasma HIV Viremia and Nadir CD4+ Cell Count in HIV-Positive Patients

Abstract: We investigated the spike IgG levels of HIV+ patients on antiretroviral therapy six months after they received their second dose (T2) and six months after the third dose (T3) of the BNT162b2 mRNA vaccine, as well as the influence of different levels of plasma HIV viremia of overall CD4+ cell count and nadir value on the humoral time course. One hundred eighty-four patients were enrolled. The median age was 55 years, the median CD4+ cell count was 639 cells/mm3 and the median nadir value was 258 cells/mm3. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The pooled IRR was 97.25% (95% CI, 93.81–99.49) in 29 studies ( 27 , 30 , 31 , 39 , 41 65 ) involving 2,599 PLWH recipients of booster vaccination, with a high degree of heterogeneity between studies ( I 2 = 93.25%) ( Table 1 ; Supplementary Table S2 ). However, subgroup analyses showed no significant differences between the groups ( p ≥ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled IRR was 97.25% (95% CI, 93.81–99.49) in 29 studies ( 27 , 30 , 31 , 39 , 41 65 ) involving 2,599 PLWH recipients of booster vaccination, with a high degree of heterogeneity between studies ( I 2 = 93.25%) ( Table 1 ; Supplementary Table S2 ). However, subgroup analyses showed no significant differences between the groups ( p ≥ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has to be underlined the unavailability of a longitudinal evaluation of neutralizing response and cellular analysis of T-cell memory response: we did not include these data in our study because of the difficulty of obtaining a large amount of blood from patients who are already regularly monitored and because of the elevated costs of such studies, which make it necessary to work in a biosafety level 3 laboratory. We identified COVID-19-naïve subjects based on self-reported data, as currently accepted [18,38]: antibody titers against the N antigen protein waned with time [39,40], and they could not be detectable after SARS-CoV-2 infection [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…NtAb titers are the best correlate of protection from severe COVID-19 [45] and live virus neutralization, despite the time consuming and requiring biosafety level 3 containment, remains the gold standard to investigate immunity in specific cohorts. In the HIV-positive population, further studies are needed to define the role of the fourth vaccine dose and what immunovirological parameters may impact the success of vaccination [38].…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been reported nadir CD4+ T cells are essential for the induction of humoral immune response of mRNA vaccine, and a nadir value ≤ 330 cells/mm 3 had 100% sensitivity in predicting a nonoptimal response. 17 This implied that vaccination with inactivated COVID-19 vaccine did not change the viral load greatly. However, some patients showed a viral blip, which we were not sure if they were related with vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Low nadir CD4+ T cell count has been regarded as the strongest factor associated with a discordant immune response and was firmly associated with immune activation and rates of intrinsic apoptosis 16 . It has been reported nadir CD4+ T cells are essential for the induction of humoral immune response of mRNA vaccine, and a nadir value ≤ 330 cells/mm 3 had 100% sensitivity in predicting a nonoptimal response 17 . From our study, nadir CD4+ T cells also showed a characteristic of predicting a weaker and shorter immune response after the second shot of inactivated vaccine.…”
Section: Discussionmentioning
confidence: 99%